Comparison of Two Circular-Stapled Techniques for Esophageal Cancer: A Propensity-Matched Analysis - Lin, Hang; Liang, Ge’ao; Chai, Huiping; Liao, Yongde; Zhang, Chunfang; Cheng, Yuanda (Frontiers in Oncology, 2021)
Objective: The optimal technique for the thoracoscopic construction of an intrathoracic esophagogastric anastomosis continues to be a subject of controversy. The aim of this study was to compare the perioperative outcomes of circular-stapled anastomosis using a transorally inserted anvil (OrvilTM) with those of circular-stapled anastomosis using a transthoracically placed anvil (non-OrvilTM) in totally minimally invasive Ivor Lewis esophagectomy (Ivor Lewis TMIE). Methods: The data of 272 patients who underwent Ivor Lewis TMIE for esophageal cancer at multiple centers were collected from January 1, 2014 to December 31, 2017. After propensity score matching (1:1) for patient baseline characteristics, 65 paired cases were selected for statistical analysis. Logistic regression analysis was performed to investigate the significant factors of anastomotic leakage. Results: In the propensity score-matched analysis, compared with the non-OrvilTM group, the OrvilTM group was associated with a significantly shorter operation time (p=0.031), less intraoperative hemorrhage (p<0.001), lower need for intraoperative transfusions (p=0.009), earlier the postoperative oral feeding time (p=0.010), longer the chest tube duration (p<0.001), shorter postoperative hospital stays (p=0.001), lower total hospitalization costs (p<0.001) and a lower postoperative anastomotic leakage rate (p=0.033). Multivariable logistic regression analysis showed that anastomotic technique and pulmonary infection were independent factors for the development of postoperative anastomotic leakage (p< 0.05). Conclusions: OrvilTM anastomosis exhibited better perioperative effects than did non-OrvilTM anastomosis after the propensity score-matched analysis. Remarkably, the OrvilTM technique contributed to a lower postoperative anastomotic leakage rate than did the non-OrvilTM technique.